The effectivities of zakat productive funds toward zakat recipient income in Palembang - Ichsan Hamidi; Suhel Suhel; Abdul Latif (Jurnal Ekonomi Pembangunan, 2019)
This study to investigate effectivities of zakat productive funds toward zakat recipient income in Palembang. Data using primary data which collect through interviews, observation, and documentation with instruments a questionnaire. The method in this study uses the quantitative approach with applying a regression model. The population in this study are all the recipients who receive the funding of zakat productive from BAZNAS of South Sumatra. The findings of this study indicated that the capital of zakat productive, length of business and training has a significant effect on zakat recipient income in Palembang city.